2019
DOI: 10.1016/j.cofs.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism and bioactive properties of chlorophylls

Abstract: Chlorophylls are fundamental molecules for life and probably the most important of all natural pigments. Although chlorophyll breakdown is inevitably associated with the loss of green color during ripening or senescence, the truth is that chlorophyll molecules continuously degrade through so-called chlorophyll turnover (lifetime of hours). In addition to their primary function, chlorophylls are in demand due to their bioactive properties. Recently, several chlorophyll derivatives have shown health promoting ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(38 citation statements)
references
References 47 publications
0
37
0
1
Order By: Relevance
“…Photosynthetic organisms predominantly present chlorophyll a and b, whereas chlorophyll c, d, and f are found exclusively in some microalgae species, algae, and photosynthetic bacteria. [ 3 , 34 ].…”
Section: Most Promising Microalgae-derived Pigments: An Overviewmentioning
confidence: 99%
“…Photosynthetic organisms predominantly present chlorophyll a and b, whereas chlorophyll c, d, and f are found exclusively in some microalgae species, algae, and photosynthetic bacteria. [ 3 , 34 ].…”
Section: Most Promising Microalgae-derived Pigments: An Overviewmentioning
confidence: 99%
“…As reviewed in Solymosi and Mysliwa-Kurdziel [28], chlorophylls are good antioxidants because of their effective scavenging activity of reactive oxygen species (ROS) and inhibition of lipid peroxidation. Chlorophylls are most commonly used as natural food colorants, but, recently, their bioactive properties [29] have become more in focus as research has shown their emerging role as potential prebiotics in rebalancing gut microbiota in mice [30].…”
Section: Effect Of Illumination On Carotenoid and Chlorophyll Contentmentioning
confidence: 99%
“…Reactive oxygen species (ROS) occur within cells in various forms such as superoxide (O2• ̶ ), hydroxyl (•OH), peroxyl (ROO•), alkoxyl (RO•), hydroperoxyl (HO2•), hydrogen peroxide (H2O2), and singlet oxygen ( 1 O2). Numerous studies have reported the antioxidant functions of chlorophylls [52,53]. The common experimental approach to assess ROS in different tissues of experimental animals (such as mice and rats) is to administer diets rich in copper chlorophyllins [53].…”
Section: Determination Of the Antioxidant Activitymentioning
confidence: 99%
“…Furthermore, the results of some studies . Numerous studies have reported the antioxidant functions of chlorophylls [52,53]. The common experimental approach to assess ROS in different tissues of experimental animals (such as mice and rats) is to administer diets rich in copper chlorophyllins [53].…”
Section: Determination Of the Antioxidant Activitymentioning
confidence: 99%